Reforma al art….10 (135) del código orgánico de la niñez y adolescencia en relación a la negativa de la parte actora de someterse a la prueba de ADN para establecer la paternidad debiéndose conceder un término prudencial y de persistir en esa negativa presumirse de hecho la no relación parento filial con sus consecuencias jurídicas - Villalta Ramírez, Joffre Hernán (2015)
Our legal system related to the Code of Childhood and Adolescence states that the court must set the alimony whose affiliation or relationship in the case of other blood relatives has not been legally established according to the following rules: "The Judge / a fix alimony for the child or adolescent to a person whose affiliation or relationship in the case of other blood relatives has not been legally established according to the following rules: a) In the event there is refusal by the defendant or defendant to submit to DNA evidence that Judge / a available, it is presumed fact parentage or kinship in the case of other blood relatives, in food and the same Order, which shall be payable from the provision of demand. From this statement this legal regime greatly harms the defendants in trials with food acknowledgment of paternity, since no equal rights of the plaintiff and the defendant are presented, thereby violating what our Ecuadorian Constitution states, that of ensure the full enjoyment of our rights without discrimination. By presenting this loophole, it is a phenomenon that affects thousands of people in our country, because the procedure does not determine or compel the plaintiff to present a DNA test on the date and time set by the court if the defendant if you do, and even that is still paying the food provisional pension from the defendant without knowing if the child is his or not, even having cases of bad faith on the part of the plaintiffs in court proceedings, relying on the best interests of child, but harming rights of the alleged father. All the people we are governed by legal rules that we must follow, and if not to have to answer for our actions, but our legal system has failed responsibilities by the Actor / a in trials with food acknowledgment of paternity. With this legal problem I bring with legal reasoning, and especially so that equality in the litigants to not being affected, nor any right that is established in our Constitution are not jeopardized